2015
DOI: 10.1016/j.jconhyd.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Using vapor phase tomography to measure the spatial distribution of vapor concentrations and flux for vadose-zone VOC sources

Abstract: A test was conducted at a chlorinated-solvent contaminated site in Tucson, AZ, to evaluate the effectiveness of vapor-phase tomography (VPT) for characterizing the distribution of volatile organic contaminants (VOC) in the vadose zone. A soil vapor extraction (SVE) system has been in operation at the site since 2007. Vapor concentration and vacuum pressure were measured at four different depths in each of four monitoring wells surrounding the extraction well. The test provided a 3D characterization of local va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In the Shenzhen factory studied here, we found that airborne TCE near a metal electroplating workshop and sewage pool were higher than the rest of the factory. The content of TCE in water (6.1 μg/L on average) was lower than that of Puerto Rico (43.6 μg/L) [ 22 ] while closer to that of the USA (3.8 μg/L) [ 23 ]. Taken in concert, the impact of occupational and environmental exposure to TCE in air has become a public health issue of general concern.…”
Section: Discussionmentioning
confidence: 99%
“…In the Shenzhen factory studied here, we found that airborne TCE near a metal electroplating workshop and sewage pool were higher than the rest of the factory. The content of TCE in water (6.1 μg/L on average) was lower than that of Puerto Rico (43.6 μg/L) [ 22 ] while closer to that of the USA (3.8 μg/L) [ 23 ]. Taken in concert, the impact of occupational and environmental exposure to TCE in air has become a public health issue of general concern.…”
Section: Discussionmentioning
confidence: 99%
“…The approach can provide a more accurate measure of vapor-phase contaminant mass discharge, characterize mass-transfer conditions, and provide a higher-resolution characterization of the groundwater source distribution ( Brusseau et al. 2010 , 2013 , 2015 ; Mainhagu et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up testing and demonstration of the methods were conducted at a Tucson, Arizona, site on the National Priorities List (NPL), which documents hazardous waste sites eligible for long-term remedial action ( Brusseau et al. 2015 ; Mainhagu et al. 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…High porosity and high permeability are beneficial to the success of SVE, mainly because they have a positive effect on the airflow rate through the soil 2 . Highly soluble pollutants and soils with high water and organic matter contents are unfavorable for SVE, and thus, it is difficult to demonstrate an improvement to the soil pollution situation using SVE in these soils 11 , 12 . Because soil pollution remediation is a relatively recent process in China, many remediation technologies are still in the laboratory experiment stage, and there has been a lack of systematic research.…”
Section: Introductionmentioning
confidence: 99%